(3JMQjQ cJGH GdcQI hGdCSWhGfIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GQTejOSs
(3ChdgG (B:s
(3GdebGdI GdChdi UOQ GdcJGH GaJM CQTejOS cJGHg HCf bGd eNGWHkG dhGMO ef Cgd ReGfg GSeg OhSjKGhS SdGe Ydjc s
(3BNQgG (B:s
(3NWhW MeGSI ddOGFQI eJdGbjI djMOK Ydi GdOGFQI Tcd eVdY hjNQL ef RhGjGg NWhWkG s
(3Vef eLehY , JQJjHgG (B: (3GdSGOS YTQs
(3GfXQ GdeNWhW Qbe (B66s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(16 / 2432) s
Keywords: (3GdQjGVjGJs